School Board Policies on Prevention and Management of Anaphylaxis in İstanbul: Where Do We Stand? - Ahmet Özen (Balkan Medical Journal, 2016)
Aims: This study was carried out to identify the current status of prevention and management of anaphylaxis in school children with the main goal of establishing such an action plan.